Influencia de la disfuncion familiar en el abandono infantil de niños y niñas atendidas en la demuna de la municipalidad provincial de pacasmayo: 2015 - Javier Ventura, Ethel Miluska (2015)
This thesis was carried out with the purpose to analyze the influence of family dysfunction in child neglect of children and girls met in the DEMUNA of the Municipality Pacasmayo Province: 2015. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 41 children of both sexes, with whom they work by applying the methods and techniques of quantitative and qualitative research. The results obtained, we can deduce that the abandonment of these boys and girls is a consequence of family situations that end with the remoteness and abuse of children by the. In many cases, the home is in charge of the older brothers or adolescents that are grouped by affinity loop. In addition we can contrast that marked the failure of family roles breeds dissatisfaction of basic needs and emotional neglect of the children served in the DEMUNA of the Municipality Pacasmayo Province:2015